Structural performance of recycled aggregate concrete-filled stainless steel tube columns - Tan, Chia Wei (Nanyang Technological University, 2020)
The structural performance of recycled aggregate concrete-filled stainless steel tube (RACFSST) columns were assessed. The experiment involved 12 RACFSST columns tested under pin-ended condition, as well as material tests and initial global geometric imperfection measurements. This report discusses the lateral deflections along the column lengths and the longitudinal strains. The EN 1994-1-1, AS 5100 and AISC 360 design codes for normal concrete-filled carbon steel tube were assessed for their applicability to RACFSST columns. All three codes yield good consistency and accuracy despite with some unsafe predictions when applied to the circular RACFSST columns.